Developing Digital-Based Islamic Religious Education Teaching Modules on the Subject Matter of Duha Prayer in Elementary Schools - Hamdi; Setria Utama Rizal; Nurul Hikmah; Muhammad Syabrina; Sulistyowati; Mualimin (Jurnal Pendidikan Agama Islam, 2024)
Purpose –  The purposes of this study are to produce digital-based Islamic religious education teaching module products developed using the eXe-Learning application and to find out whether digital-based Islamic Religious Education teaching module products are feasible to use in learning. Design/methods/approach – This study used development research (Research and Development) with the 4D development model (Define, Design, Development, and Dissemination). At the design validation stage, the digital-based Islamic Religious Education teaching module was validated by material experts and media experts. Data collection techniques used questionnaire instruments Findings – The assessment by the material experts, consisting of 16 aspects, was 90% categorized as very feasible. The evaluation by the first media expert, consisting of 20 aspects, was 82% categorized as very feasible. The second media expert validation, as a whole, was 96% categorized as “very feasible.” The average value of material and media experts was 89.33% (Very Feasible). Meanwhile, the student response to the digital-based Islamic Religious Education teaching module, consisting of 12 aspects, obtained 67.2%, including the “feasible” category. Moreover, in terms of the module's effectiveness in learning, it had an effect in the form of increasing student skills in performing the Duha prayer. Research implications/limitations – The implications of this development research practically have contributed to producing digital-based PAI teaching module products on the Duha prayer material used in learning. The main field trial was limited to Class IV of SDIT Al-Furqon Palangka Raya. Originality/value –  This development research supports the implementation of the Merdeka Curriculum in fulfilling the learning tools for the Merdeka Curriculum teaching modules, allowing it to contribute to the world of education